Determinants of successful FAMA’s entrepreneur at Kuala Terengganu / Nur Zainatulhani Mohamad - Mohamad, Nur Zainatulhani (Faculty of Business and Management, 2015)
The study seeks to determine the personal characteristics or personal traits that are important for entrepreneurs to become successful. Along with the vigorous economic development nowadays, it shown that Malaysia is leading the economic sectors just like the other nearest Asian country like Singapore, Brunei, Vietnam and Thailand. The factors that lead to the economic development are the rises of entrepreneurs regardless of their size. From small sized entrepreneur to the well developed entrepreneur, it does help in generate our national incomes. To reach the international scope, first the entrepreneurs themselves must know, understand and utilize the ability that they posses. As for that, this research study wants to explore the factors that lead an entrepreneur towards success. It focuses on the personal traits that they possess. There are three factors from personal traits are derived in this study which are the entrepreneur self-dependent, passion and tolerance of ambiguity. The theory and results indicate that proper measurement of those traits helps the entrepreneur to become successful. While among three factors, passion plays the vital reason towards the success of the entrepreneurs. The implications of the traits are discussed. The limitations and the suggestions for future research are also being discussed as well. In addition, this research focuses on the entrepreneurs which are under supervision of Federal Agricultural Marketing Authority (FAMA). On top of that, this research utilized 100 respondents as the samples. The method used in this study is survey questionnaire. SPSS was used in analyzing the data. Descriptive statistics, regression and reliability test analysis is applied to measure the components of each variable. The result shows that passion influent the success of the entrepreneurs the most.